Modification of the existing maximum residue level for acibenzolar‐S‐methyl in kiwi fruits. (22nd September 2017) - ,; Brancato, Alba; Brocca, Daniela; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Janossy, Judit; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta France SAS submitted a request to the competent national authority in France to modify the existing maximum residue level (MRL) for the active substance in kiwi fruits. The data submitted in support of the request were found to be sufficient to derive a MRL proposal for the crop under consideration. Adequate analytical methods for enforcement are available to control the residues of acibenzolar‐ S ‐methyl in the plant matrix under consideration. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of acibenzolar‐ S ‐methyl according to the reported agricultural practice is unlikely to present a risk to consumer health.